Reaksi Pasar Modal Terhadap Undang-Undang Republik Indonesia No. 11 Tahun 2016 Tentang Pengampunan Pajak - Prihastini, Made Ari; Herkulanus, Bambang Suprasto (E-Jurnal Akuntansi, 2017)
The aim of this research is to analyze the market reaction on Indonesian Law no 11 2016 about Tax Amnesty. The market reaction is measured using abnormal return which happens in a company including the LQ45 index. To determine the sample, this research is using non probability sampling with purposing sampling technique. The data collection is done by observation non participant method. The analysis technique is Paired Sample t-test where the observation period is 7 days using SPSS tools. Based on the research, there is no reaction by the investors in the stock market regarding the  tax amnesty law which is proven by there is no different in abnormal return before and after the announcement of tax amnesty law.